PROTECTION AND PRESERVATION SEA ENVIRONMENT IN INTERNATIONAL LAW PERSPECTIVE - Djatmiko, Agoes; Pudyastiwi, Elisabeth (Jurnal Komunikasi Hukum, 2020)
Protection of the marine environment within the framework of international law is actually an accumulation of The Principle of National Sovereignity and The Freedom of High Sea. The International Maritime Organization (IMO) states that "a right on the part of an astat threatened with the environmental injury from sources beyond its territorial jurisdiction, at least where those sources are located on the high seas, to take reasonable action to prevent or abate that injury ". The general principle of good neighbor liness can be found in international customary law as well as in Article 74 of the UN Charter. This principle is reflected in several international treaties and is supported by the country's main practices in dangerous and emergency activities. Cooperation is contained in the 24th Principle of the Stockholm Declaration and the 27th Principle of the Rio Declaration which states that countries must cooperate in the principles of good faith and the spirit of partnership as efforts to protect the environment. Keywords: protection of the marine environment, principles of good faith, International Maritime Organization (IMO)